A Strategic Action Plan for Building Modern Industry Colleges at Jiangxi University of Technology in China: Insights from Stakeholder Assessments - Libo-on, Rowena; Mingmin, Zou; Maoyun, Xu (Journal of Interdisciplinary Perspectives, 2025)
This study examines the current status, challenges, and developmental pathways of Modern Industry Colleges (MICs) at Jiangxi University of Technology (JUT) in China, to craft a strategic action plan that supports sustainable higher education reform. MICs envisioned as collaborative platforms between academia and industry are central to aligning education with regional economic needs and national innovation strategies. Despite growing policy attention, empirical studies on stakeholder perceptions remain limited. This research addresses that gap through a comprehensive survey-correlational design involving 360 stakeholders, including students, faculty, industry staff, government officials, and community members. Using a validated instrument (Cronbach's α = .978), the findings reveal that MICs are perceived to be in a "Fair" state (M = 2.50), "Moderately Challenging" to develop (M = 2.62), and "Somewhat Promising" in terms of prospects (M = 2.57). Significant positive correlations were found among status, challenges, and pathways (r = .524–.680, p < .001), highlighting the interconnectedness of these dimensions. Based on the results, the study proposes a multi-faceted strategic action plan comprising six thematic areas and over 30 targeted initiatives focused on strategic governance, curriculum innovation, faculty development, industry partnerships, infrastructure modernization, and policy advocacy. The study contributes to academic literature and institutional practice by offering a replicable framework grounded in stakeholder engagement and systems theory. It underscores the urgent need for policy synergy, continuous stakeholder feedback, and university-industry collaboration to transform MICs into engines of innovation, talent development, and regional growth.